The ratio between collagenase class I and class II influences the efficient islet release from the rat pancreas. - Brandhorst, H; Raemsch-Guenther, N; Raemsch, C; Friedrich, O; Huettler, S; Kurfuerst, M; Korsgren, O; Brandhorst, D (2008)
BACKGROUND: Previous studies indicated different roles of collagenase class I, class II and neutral protease in the enzymatic islet release from pancreatic tissue. Because no information has been available, this study was aimed to investigate the isolation efficiency of different ratios between collagenase class II and I (C-ratio) in the rat pancreas serving as model for the human pancreas without being restricted by the large variability observed in human donors. METHODS: Rat pancreata were digested using a marginal neutral protease activity and 20 PZ-U of purified collagenase classes recombined to create a C-ratio of 0.5, 1.0, or 1.5. Collagenase efficiency was evaluated in terms of isolation outcome and posttransplantation function in diabetic nude mice. RESULTS: The highest yield of freshly isolated islets was obtained using a C-ratio of 1.0. Purity and fragmentation of freshly isolated islets were not influenced by the C-ratio. After 24-hr culture performed for quality assessment, a marginal but significant reduction of viability was observed in islets isolated by means of a C-ratio of 0.5 and 1.5. Islet in vitro and posttransplantation function revealed no negative effect mediated by different C-ratios. CONCLUSIONS: The present study demonstrates that the C-ratio is of significant relevance for the outcome after enzymatic rat islet isolation. The data indicate further that purified collagenase class I or class II does not damage islet tissue even if used in excess. The present study can serve as a start for subsequent experiments in the human pancreas.